ABCB1 C3435T polymorphism and the risk of resistance to antiepileptic drugs in epilepsy: a systematic review and meta-analysis. - Haerian, B.S.; Roslan, H.; Raymond, A.A.; Tan, C.T.; Lim, K.S.; Zulkifli, S.Z.; Mohamed, E.H.M.; Tan, H.J.; Mohamed, Z. (2010)
We failed to show an association between the ABCB1 C3435T polymorphism and the risk of drug-resistance suggesting a revision in contribution of this polymorphism in the multi-drug transporters hypothesis of pharmacoresistance to AEDs in epilepsy.